Correction: Genetic divergence of Clematis alpina in the Swiss Prealps: a tale of the margins - Sofia Christe; Luca Champoud; Laurence Fazan; Michał Ronikier; Mathieu Perret; Gregor Kozlowski; Camille Christe (Alpine Botany, 2025)

Genetic divergence of Clematis alpina in the Swiss Prealps: a tale of the margins - Sofia Stefani; Luca Champoud; Laurence Fazan; Michał Ronikier; Mathieu Perret; Gregor Kozlowski; Camille Christe (Alpine Botany, 2025)
The alpine clematis ( Clematis alpina L., Ranunculaceae) is a liana growing in mountain regions of northern Eurasia. In the European Alpine region, where the subspecies C. alpina subsp. alpina occurs, a few populations are isolated from the main range in the peripheral north-western Prealps, a relatively understudied but biogeographically important region. It has been shown that such edge populations could potentially contain a source of unique genetic variability that reflects past biogeographical and microevolutionary processes. We tested this hypothesis using sequence capture data and a large population sampling across the species range. We show that individuals from the north-western Prealps form a genetic cluster that is clearly distinct from the other individuals of the European subspecies C. alpina subsp. alpina. This cluster adds to two other geographically driven clusters with a larger spatial extent, that include populations from the rest of the Alps and from the Carpathians/Balkan Peninsula mountains, respectively. Genetic diversity indices such as inbreeding and nucleotide diversity are the highest and lowest, respectively, for the Prealps populations indicating a possible loss of diversity. Our results demonstrate the biogeographical importance of isolated, marginal populations as sources of distinctive lineages, and highlight the conservation value of the north-western Prealps populations of alpine clematis. They also point out the promising use of sequence capture of gene selected for studies at high phylogenetic level for studies at intraspecific level.